Analisis Prinsip dan Faktor Produksi dalam Ekonomi Islam pada “Muza Konveksi” di Kecamatan Sumberpucung, Kabupaten Malang - Ana Nurwakhidah; Mamlu’atul Munawaroh (Alkasb: Journal of Islamic Economics, 2023)
In economic activities known as production activities, producers contribute to the creation of goods. This production activity's goals are to satisfy consumer demand and generate profits for the producers. In Islamic economics, production refers to any actions taken to achieve or enhance profits by utilizing the sources of gain supplied by Allah SWT to meet the requirements of the community. As a result, production efforts must be focused on meeting these demands. The main topic of this study is how "Muza Convection" applies Islamic economic ideas and production parameters. This study's methodology combines a qualitative descriptive approach with field research to learn more about the Muza Convection production process and determine whether or not it complies with Islamic economic principles. The data used as references in this study are actual field observations. Information gleaned via observations, interviews, and documentation it was discovered from the investigation that Muza Convection's manufacturing method involves several processes, including the stages of making designs, cutting, sewing, printing or embroidery, packing, and the last operation, which is distributing items. In addition, the production variables, starting with company capital, labor, land, and capacities and skills, are in line with Islamic Economics' production principles.